The Sacred Heart of Jesus The Visual Evolution of a Devotion - Morgan, David (Meertens Ethnology Cahiers, 2008)
Devotion to the Sacred Heart of Jesus has been controversial from its beginning in the life of the French Visitationist nun Margaret Mary Alacoque (1647-1690), who established the devotion after a series of mystical visions of Christ. Under the leadership of Sister Sophie Barat, founder of the Society of the Sacred Heart in 1800, the devotion was taken around the world in the course of the nineteenth century. Wherever it went, the devotion took the shape of an evolving visual culture. Even during Alacoque's lifetime, imagery was a fundamental part of practicing the devotion. The Sacred Heart of Jesus traces the unfolding visual biography of the Sacred Heart, showing how imagery and visual practice document the history of the devotion and the remarkable range of its evolution.